Involvement of TLR4 in the protective effect of intra-articular administration of curcumin on rat experimental osteoarthritis - Yan,Dan (2019)
Abstract Purpose In view of the principal role of Toll-like receptor 4 (TLR4) in mediating sterile inflammatory response contributing to osteoarthritis (OA) pathogenesis, we used lipopolysaccharide (LPS), a known TLR4 activator, to clarify whether modulation of TLR4 contributed to the protective actions of intra-articular administration of curcumin in a classical rat OA model surgically induced by anterior cruciate ligament transection (ACLT). Methods The rats underwent ACLT and received 50μl of curcumin at the concentration of 1 mg mL-1 and 10 μg LPS by intra-articular injection once a week for 8 weeks. Morphological changes of the cartilage and synovial tissues were observed. Apoptotic chondrocytes were detected using TUNEL assay. The concentrations of IL-1β and TNF-ɑ in synovial fluid were determined using ELISA kits. The mRNA and protein expression levels of TLR4 and NF-κB p65 were detected by real-time PCR and Western blotting, respectively. Results Intra-articular administration of curcumin significantly improved articular cartilage injury, suppressed synovial inflammation and down-regulated the overexpression of TLR4 and its downstream NF-κB caused by LPS-induced TLR4 activation in rat osteoarthritic knees. Conclusion The data suggested that the inhibition of TLR4 signal might be an important mechanism underlying a protective effect of local curcumin administration on OA.